AI, Ethics, and Education: The Pioneering Path of Sidekick Academy - Radday, Elizabeth; Mervis, Matt (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Generative artificial intelligence (AI) is swiftly cementing its role as an indispensable tool for students transitioning from K-12 to higher education and professional spheres. Yet, harnessing its full potential requires more than mere familiarity. Students must be equipped with the skills to engage with AI both productively and ethically. Left unchecked, AI usage can pose risks, especially if students lack proper guidance or understanding of their actions. Moreover, effective interaction with AI necessitates skills in prompt engineering to yield desired outcomes. Sidekick Academy is a digital online platform where students can safely experiment with and learn about AI. This article delves into the genesis of Sidekick Academy, offering a glimpse into its lessons on how to use AI and complex debate on ethical use. It also sheds light on the academy’s "sandbox" - a secure space for students to explore AI without jeopardizing their safety or privacy.